ENTREPRENEURIAL TRANSFORMATION IN THE MA'HAD ALY SYSTEM OF THE TAREKAT IDRISYIAH: BUILDING SPIRITUAL INDEPENDENCE AND ENTREPRENEURSHIP - Siswoyo, Siswoyo Aris Munandar (The Ministry of Religious Affairs, The Republic of Indonesia, 2023)
One of the tarekat that is followed and popular among Muslims in Indonesia is the Al-Idrisiyyah Order which is centered at the Idrisiyyah Islamic Boarding School Tasikmalaya. Apart from managing education, Idrisiyyah Islamic Boarding School also currently has a focus on the economy by having a mini market called Qini Mart. Seeing the education system implemented in this Islamic boarding school, it is very interesting for the author to know and research more deeply about the role of the Tarekat Al-Idrisiyyah in the academic field (education) for the State of Indonesia. This research was conducted using a qualitative descriptive method with an emphasis on the power of data analysis on existing data sources, so that the research results are not in the form of numbers but in the form of interpretations and words. Data collection techniques were carried out through observation, interviews and documentation. The results of this study are that Sufi Entrepreneurs are the choice of the Al-Idrisiyyah order indeveloping its various business lines. The congregation which is located in Cisayong, Kab. Tasikmalaya has successfully applied it. Such as in the fields of creative livestock, agriculture, department stores, Qini Mart, to places to eat and take part in fostering the economy of local residents with cooperatives and also form the Baitul Mall Wattawamil (BMT).